The insight of trust engineering for 21st century organizations - Simon Samwel Msanjila (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
The effective smoothening factor in different forms of collaboration has proven to be getting trustworthy partner organizations. Nowadays, trust among the 21st century organizations should be analyzed and assessed with a look from a different angle than how it has been conceptualized and addressed for such organizations in the past. In the past as it has been commonly practiced, the concept of trust has been addressed considering one chosen criterion which in most cases is subjective and not measurable. The trust analysis has also been performed at the level of one actor such as individual or organization without any comparativeness to other actors. In practice, also trustworthiness in an actor has been assumed to be a phenomenon that naturally emerges rather than being created. Furthermore, in past research, trust has been considered to be a subjective aspect and emerging from opinions and recommendations from other peers. On these bases it has been difficult to justify the rationality of trust attached to an actor for collaboration. Today the concept of trust has become an amenable factor for smoothening inter-organizational collaboration and thus has raised the need to enhance the rationality in trustworthiness measurements. Therefore, the 21st century organizations need to reconsider their working approach with incorporating trust creation and enhancement strategies. This article surveys existing work on inter-organizational trust addressing the complementary and contradictory concepts, as well as different practices in various disciplines. The article then analyzes the trust criteria and approaches for assessment of trust in organization during this 21st century.
Keywords: 650; trustworthy organizations; trustworthiness; trust; collaborative networks; new face organizations